Rebranding Technical Vocational Education and Training; Youth Education for Vocational Careers, Kenya - Kanyoro, Kamau; Nancy, Chege; Sophia, Bironga (My University, 2013)
The aim of this paper is to revolutionize the approach of Technical and vocational training in Kenya, in regards to character and attitude change. The specific objective is to create awareness on the importance of Technical training in Developing countries. For any country to industrialize, as has been demonstrated by industrialized countries like Japan, Canada, Singapore and the USA, the key focus is technical and vocational training which produces technicians and artisan, the engine drivers of industrialization. This paper proposes a paradigm and mentality shift in Technical and vocational training approaches including; 1) Re-training of instructors/Trainers 2) use of pure practical approaches in training and integrating modern ICT approaches in training 3) Restrengthening of affective domain of learning in training with aim of producing technicians and artisans who are holistically trained but very strong in character.
Keywords: Affective; psychomotor; cognitive; andragogy; pedagogy; technology